Strategi Deep Learning Dalam Pembelajaran Menulis Untuk Mengembangkan Berpikir Kritis Dan Kreatif Siswa - Sakinah Fitri; Anita Candra Dewi (FKIP UNSULTRA, 2026)
Writing instruction is a strategic tool for developing students' critical and creative thinking skills. However, writing instruction in schools remains largely procedural and emphasizes technical aspects of language, thus under-motivating students to think deeply. This article aims to systematically examine deep learning strategies in writing instruction and their contribution to the development of students' critical and creative thinking. The research employed a literature review method with a descriptive qualitative approach. Data sources were national and international journal articles published between 2018 and 2025 and relevant to the topics of writing instruction, deep learning, and Higher Order Thinking Skills (HOTS). Data were collected through database searches such as Google Scholar, DOAJ, and Sinta, and then analyzed using thematic analysis techniques. The study's results indicate that deep learning strategies in writing instruction can improve critical thinking skills through reflection, discussion, and analysis prior to writing. Furthermore, this approach fosters student creativity by generating more original and diverse ideas. Writing instruction based on real-world contexts has also been shown to increase student engagement and motivation. The writing process serves as a vehicle for HOTS development, rather than simply language practice, and the teacher's role shifts to that of a thinking facilitator guiding students' exploration of ideas and reflection. Thus, the application of deep learning strategies in writing learning has great potential to create a learning process that is meaningful, contextual, and relevant to the demands of 21st-century education.